Penerapan Unsur Visual Bentuk Tanduk Domba Garut Dalam Desain Busana Siap Pakai - Pratiwi Kusumowardhani; Larastika Rachmawati Hakim (JURNAL RUPA, 2017)
Fashion design is now being raised on culture, flora, fauna, and local knowledge of the archipelago with a style that is more trendy and dynamic. The uniqueness of Indonesia who brought fashion popular in foreign countries. One of the unique fauna that Indonesia and must be preserved is the Garut sheep. Garut sheep or Ovis aries is an Indonesian fauna originating from Leles, Wanaraja, and Limbangan Garut district. Characteristic of Garut sheep horn has a circular shape (large and thick) are strong, tall body, strong, and large compared to other types of sheep. Garut sheep ram with horns larger, circular, and stronger than the females horn. Sheep fighter also has a unique necklace. Sheep are usually used to fight fights Garut sheep, used the meat for consumption as well as the skin used for the various needs of fashion. The methodology of this research is an exploration, and analysis based on literature sources based on the elements and principles of design by Mayall Theory. In this research, the writer limits design analysis domba Garut in Indonesia on horn sheep arrowroot, which raises moodboard, as a reference for the manufacture of alternative fashion design selected.